The Effect Of Work Motivation And Knowledge Management On Increasing Innovativeness - Budi Santoso , Arief; Moeins, Anoesyrwan; Sunaryo, Widodo (International Journal of Educational Research & Social Sciences, 2022)
This study aims to analyze the effect of work motivation and knowledge management on increasing the innovation of ASN at the Central Ministry of Transportation. The number of samples in this study were 249 respondents using the slovin technique from all units in the Ministry of Transportation. Data was collected using questionnaires, observations and interviews with related parties. The data analysis technique used is the mix method with multiple linear regression analysis and indicator analysis.The results showed that the variables of Work Motivation and knowledge management partially and simultaneously had a positive effect on Employee Innovativeness at a significance level of 0.05 with a regression coefficient of respectively.The value of the regression equation is Y 42.013 0.490X1 0.166X 2 , this indicates that an increase in one level of Work Motivation will result in an increase in Innovativeness of 0.528 at a constant 42.013, and each increase in one level of Knowledge Management will result in an increase in Innovativeness 0.132 at a constant 42.013. With an adjusted R-Square value of 0.282, it means that the effect is 28.2%. Thus, strengthening work motivation and knowledge management together with innovation will increase employee innovativeness.